Prophets, pegon, and piety; The Javanese Layang Ambiya - Ricci, Ronit (UI Scholars Hub, 2021)
The tales of the prophets are among the most popular textual traditions across the Islamic world and Java proves no exception. Beginning with the first human and first prophet Nabi Adam, these often vast collections recount the biographies of all those viewed as prophets in Islam, ultimately leading up to the “seal of the prophets”, Muhammad. Many manuscripts of this genre were composed and copied in Javanese, in different periods, locales, and milieus, opening a window to how these core Islamic stories and the messages they carry were understood and transmitted in Java. The essay explores one example, a Layang Ambiya composed in the pĕsantren milieu in the mid-nineteenth century and written in pegon (MSB L12), currently housed in the Museum Sonobudoyo, Yogyakarta.